Improving the performance of a bobsleigh by aerodynamic optimization - Winkler, A.; Pernpeintner, A. (The Engineering of sport 7, Volume 2, 2008)
The performance of a bobsleigh is significantly affected by its aerodynamic properties. As it is typical for bluff bodies, the aerodynamic drag of a bobsleigh consists primarily of pressure drag and is dominated by its shape. The shape design of a bobsleigh is commonly based on intuitive shape modifications resulting from individual experiences of the athletes. This paper aims to present the process of optimizing the aerodynamic drag with tools used in road vehicle and race car aerodynamics. The starting point in the process has been the development of a parametric three-dimensional CAD-model including a simplified shape of the crew. Therewith varying bobsleigh versions have been created taking into account the geometric restrictions given by the regulations of the international bobsleigh federation (FIBT). Extensive CFD simulations have been performed to examine the flow and the aerodynamic forces acting on the respective shapes under racing conditions. This method has been applied in the preliminary design process whereas for the sake of the detail optimization additional wind tunnel tests on a 1:3 model scale have been performed. This was due to the fact that the examination of minor changes to the hob shape is more time consuming in CFD than using a proper wind tunnel model. The wind tunnel tests were also used for validating the CFD results. The findings of the wind tunnel experiments have been incorporated into the CAD model and a final optimized bob shape has been created. Further wind tunnel tests on a full scale prototype are planned to find out the ideal seat position and posture of the crew and to validate the previous computational and experimental results.